Improved outcomes of acute lymphoblastic leukemia after allogeneic blood or marrow transplantation with high-dose post-transplantation cyclophosphamide in the era of more effective pre-transplant therapy - Jonathan A. Webster; Madison Reed; Hua-Ling Tsai; Philip H. Imus; Douglas B. Smith; Alexander J. Ambinder; Mark J. Levis; Amy E. DeZern; Gabrielle T. Prince; Tania Jain; Javier Bolaños-Meade; Lukasz P. Gondek; et al. (Haematologica)
The therapeutic landscape in ALL has changed dramatically over the last decade. Allogeneic blood or marrow transplantation (AlloBMT) has also evolved and remains an important option for consolidation. We assessed the interplay between these factors by analyzing the outcomes of 251 adult ALL (214 B and 37 T ALL) patients undergoing alloBMT with post-transplantation cyclophosphamide (PTCy) across two eras: 2008-2014 (ERA1) and 2015-2022 (ERA2). ERA1 patients were younger (median age 45.5 vs. 50, p=0.03), less likely to have an HCT-CI ≥4 (9% vs. 21%, p=0.01), more likely to have MRD by flow cytometry (20% vs. 9%, p=0.01) and receive myeloablative conditioning (56% vs. 3%, p